Mistakes in the shooting training by adolescent biathletes - Vukov, V. Y. (Physical Education, Sport and Kinetotherapy Journal, 2022)
In this article we are going to find out the major mistakes in the shooting technique of young biathletes, and the possibilities consequences of them. The purpose of our development is the determination of the main mistakes in the shooting technique and analysis of their possible consequences. The main tasks of the research are: to study the theoretical and methodological literature on the research problem; pedagogical observation, to check the opinion of coaches regarding the basic shooting mistakes in biathlon. The following research methods were used to establish the results: bibliographic analysis of the specialized literature on the problem, pedagogical observation, conversation with biathlon coaches. In this list, the mistakes and their consequences appear incomplete. In Table 1., only the main ones are presented and most common mistakes allowed in the implementation of shooting in adolescent biathletes. It is observed in adolescence poor absorption of the technical elements of shooting. The given table can be used by coaches and athletes to define of shooting in teenage biathletes.